Phase II study results of a replacement therapy for hereditary angioedema with subcutaneous C1‐inhibitor concentrate. Issue 10 (11th August 2015) - Zuraw, B. L.; Cicardi, M.; Longhurst, H. J.; Bernstein, J. A.; Li, H. H.; Magerl, M.; Martinez‐Saguer, I.; Rehman, S. M. M.; Staubach, P.; Feuersenger, H.; Parasrampuria, R.; Sidhu, J.; et al.
Abstract Background Hereditary angioedema (HAE) due to C1 inhibitor deficiency manifests as recurrent swelling attacks that can be disabling and sometimes fatal. Long‐term prophylaxis with twice‐weekly intravenous injections of plasma‐derived C1‐inhibitor (pdC1‐INH) has been established as an effective treatment. Subcutaneous (SC) administration of pdC1‐INH has not been studied in patients with HAE. Methods This open‐label, dose‐ranging, crossover study (COMPACT Phase II) was conducted in 18 patients with type I or II HAE who received two of twice‐weekly 1500, 3000, or 6000 IU SC doses of highly concentrated volume‐reduced CSL830 for 4 weeks each. The mean trough plasma levels of C1‐INH functional activity, C1‐INH and C4 antigen levels during Week 4, and overall safety and tolerability were evaluated. The primary outcome was model‐derived steady‐state trough C1‐INH functional activity. Results After SC CSL830 administration, a dose‐dependent increase in trough functional C1‐INH activity was observed. C1‐INH and C4 levels both increased. The two highest dose groups (3000 and 6000 IU) achieved constant C1‐INH activity levels above 40% values, a threshold that was assumed to provide clinical protection against angioedema attacks. Compared with intravenous injection, pdC1‐INH SC injection with CSL830 showed a lower peak‐to‐trough ratio and more consistent exposures. All doses were well tolerated. Mild‐to‐moderate local site reactions were noted with pain and swelling being the most common adverse event. Conclusions Subcutaneous volume‐reduced CSL830 was well tolerated and led to a dose‐dependent increase in physiologically relevant functional C1‐INH plasma levels. A clinical outcome study of SC CSL830 in patients with HAE warrants further investigation.